Metals : materials for inspirational design. - Lefteri, Chris, ....- (Mies : Rotovision, 2004)
Metals continues in the tradition of the Materials series by bringing to people's attention a range of inspirational products and materials that challenge the boundaries of traditional application. It includes both everyday and familiar products and those that are new, exciting, and unexpected. Hugely visual and easily accessible, even to those with no prior knowledge of the material, Metals introduces each application with authorial comment as well as interviews with the designers and manufacturers. Examples are featured from the areas of packaging, product design and architecture. This is coupled with detailed technical specification tables, an internal index that points the way to linked pages of interest, and an extended glossary and resources section for more in-depth study.
Keywords: Industrieel ontwerpen; Metalen